Staphylococcus aureus colonization and risk of surgical site infection in children undergoing clean elective surgery: A cohort study. Issue 27 (July 2018) - Esposito, Susanna; Terranova, Leonardo; Macchini, Francesco; Bianchini, Sonia; Biffi, Giulia; Viganò, Martino; Pelucchi, Claudio; Leva, Ernesto; Principi, Nicola
Abstract : Abstract: Staphylococcus aureus persistently colonizes the skin and nasopharynx of approximately 20% to 30% of individuals, with the highest rates in younger children. To avoid clinical problems for carriers and the spread of S aureus to other hospitalized patients, screening and decolonization of carriers undergoing surgery has been recommended. However, the best approach to patients undergoing clean surgery is not precisely defined. To evaluate whether children carrying S aureus admitted to the hospital for clean elective surgery have an increased risk of postoperative surgical infections, 393 infants and children (77.1% males; mean age ± standard deviation, 7.6 ± 4.5 years) who were scheduled for clean elective surgery procedures were evaluated for S aureus carriage on the day of intervention and 5 days after it. Both anterior nares and pharyngeal swabs were collected. S aureus was identified using the RIDAGENE methicillin-resistant S aureus (MRSA) system (R-Biopharm AG, Darmstadt, Germany), according to the manufacturer's instructions. At admission, 138 (35.1%) children screened positive for S aureus . MRSA was identified in 40 (29.0% of S aureus positive subjects) cases. The carriage rates of S aureus and MRSA varied considerably with age, and in children <2 years old the rate was significantly lower than in any other age group ( P <  .05). Surgical site infection was demonstrated in 4 out of 109 (3.7%) children who were initially colonized by S aureus and in 5 out of 201 (2.5%) children with a negative screening, without any statistically significant difference between groups ( P =  .72). None of these children had MRSA. These results seem to suggest that children undergoing clean elective surgery do not need to be screened for S aureus colonization because, although positive, they have no increased risk of surgical site infection. Following this statement, preoperative procedures should be simplified with relevant advantages from a clinical, social, and economic point of view.